The Expression of von Willebrand Factor-Binding Protein Determines Joint-Invading Capacity of Staphylococcus aureus, a Core Mechanism of Septic Arthritis - Manli Na (American Society for Microbiology, 2020)
ABSTRACT Septic arthritis, one of the most dangerous joint diseases, is predominantly caused by Staphylococcus aureus. In contrast, coagulase-negative staphylococci are rarely found in septic arthritis. We hypothesize that coagulases released by S. aureus, including coagulase (Coa) and von Willebrand factor-binding protein (vWbp), play potent roles in the induction of septic arthritis. Four isogenic S. aureus strains differing in expression of coagulases (wild-type [WT] Newman, Δcoa, Δvwb, and Δcoa Δvwb) were used to induce septic arthritis in both wild-type and von Willebrand factor (vWF)-deficient mice. Septic arthritis severity was greatly reduced when wild-type mice were infected with the Δcoa Δvwb and Δvwb variants compared to WT or Δcoa strains, suggesting that vWbp rather than Coa is a major virulence factor in S. aureus septic arthritis. vWF-deficient mice were more susceptible to bone damage in septic arthritis, especially when the Δvwb strain was used. Importantly, no difference in arthritis severity between the Δvwb and WT strains was observed in vWF-deficient mice. Collectively, we conclude that vWbp production by S. aureus enhances staphylococcal septic arthritis. IMPORTANCE Septic arthritis remains one of the most dangerous joint diseases with a rapidly progressive disease character. Despite advances in the use of antibiotics, permanent reductions in joint function due to joint deformation and deleterious contractures occur in up to 50% of patients with septic arthritis. So far, it is still largely unknown how S. aureus initiates and establishes joint infection. Here, we demonstrate that von Willebrand factor-binding protein expressed by S. aureus facilitates the initiation of septic arthritis. Such effect might be mediated through its interaction with a host factor (von Willebrand factor). Our finding contributes significantly to the full understanding of septic arthritis etiology and will pave the way for new therapeutic modalities for this devastating disease.